A taxonomic study of Methocha Latreille (Hymenoptera: Tiphiidae: Methochinae) from India with description of three new species - Hanima, Raveendran K.p.; Kumar, P. Girish; Binoy, C.; Sureshan, P.m. (Zootaxa, 2021)
The genus Methocha Latreille (Hymenoptera: Tiphiidae) from India was studied, resulting in the description of a new species based on females, Methocha krombeini Hanima, Girish Kumar & Binoy sp. nov., and two new species based on males, M. paraceylonica Hanima, Girish Kumar & Binoy sp. nov., and M. shyamagatra Hanima, Girish Kumar & Sureshan sp. nov. from India. A key to species of Methocha occurring in the Indian subcontinent is provided.